Hypernatremia post hydatid cyst resection: case report - Sharma, S. P.; Pathak, Nishant; Grewal, Ritu; Singh, Anuj (International Surgery Journal, 2021)
Hypernatremia or increased sodium level is defined as the plasma sodium level over 145 m mol/l. The electrolyte abnormality is associated with severe mortality (40-60%). Patients presenting acutely with this entity have varied clinical spectrum ranging from unresponsive state, dysphagia, shortness of breath, vomiting to seizures, coma or to even death. Iatrogenic hypernatremia usually a rare entity ensues after usage of hypertonic saline as scolicidal agent during hydatid cyst resection surgeries. There is a need of high level of suspicion, to be maintained in all patients being managed for clinical conditions requiring use of hypertonic saline (3-20% NS). Here we present a case of iatrogenic hypernatremia, post-surgical resection of hydatid cyst, with clinical manifestation and subsequent management in our tertiary care hospital.